Implementation of the PBL Learning Model in Class V Mathematics at SD Negeri Sari 1 - Budi Setyani; Murtono Murtono; Slamet Utomo (INOPENDAS: Jurnal Ilmiah Kependidikan, 2021)
This study aims to determine the implementation of the PBL learning model. This learning model aims to improve student learning outcomes in the material of distance, time, and speed in class V SD Negeri Sari 1, Gajah District, Demak Regency. In this study, an experimental method with a quantitative approach was used and research techniques through tests with the research site in class V SD Negeri Sari 1. In data collection, tests, documentation and interviews were used. Data analysis using qualitative descriptive analysis. Based on the results of research conducted, the application of the PBL learning model to improve student learning outcomes in the material of Distance, Time, and Speed in Class V Elementary Schools has stages in its learning activities. Conclusion In its implementation, it is known that students are more creative and enthusiastic in the learning process of Mathematics, the material for distance, time, and speed, and student learning outcomes have increased quite high.